Cytotoxicity test of chicken eggshell-based hydroxyapatite on human dental pulp cells - Utama, Jeremy; Elline, Elline; Subrata, Aryadi; Prahasti, Anastasia Elsa; Azman, Syuwari Azhar (Wolters Kluwer – Medknow, 2023)
Background: Materials such as calcium hydroxide [Ca(OH)2] are commonly used for vital pulp therapy in dentistry, but they have some limitations. Hydroxyapatite (HA) is able to induce reparative dentin; therefore, it can be used as an alternative to Ca(OH)2 for pulp treatment. However, pulp treatment materials should have some ideal characteristics, including low toxicity. The toxicity test is essential to ensure the biological safety of pulp treatment materials. Objective: To determine the toxicity of various concentrations of HA derived from eggshell waste to human dental pulp stem cells (hDPSCs). Methods: We determined the viability of the hDPSCs after exposure to 1%, 2%, or 4% HA by the diphenyl-2H-tetrazolium bromide assay method to measure cell viability and using an enzyme-linked immunosorbent assay reader to calculate the optical density. Results: The viability values of the hDPSCs exposed to 1%, 2%, and 4% HA were 84.1%, 86.75%, and 95.03%, respectively. HA concentration had no significant effect on hDPSC proliferation. Conclusion: Chicken eggshell HA is a nontoxic material that has the potential to support human dental pulp cell proliferation, which is one of the essential criteria for a pulp treatment material.